Distribution of different Skeletal pattern in Patients seeking Orthodontic Treatment in Mid-western Nepal - Halwai, Hemant Kumar; Gautam, Vanita; Pandey, Manju (Orthodontic Journal of Nepal, 2016)
Objective: To determine the distribution of different skeletal pattern in orthodontic patients visiting a tertiary center in midwestern Nepal. Materials & Method: A sample of 200 lateral cephalograms of Nepali patients visiting UCMS-College of Dental Surgery, Bhairahawa was obtained. The jaw base relationship was assessed from lateral cephalograms using angular measurement (ANB angle). Among the total sample size; 74 (37%) were males and 126 (63%) were female. Age was divided into 3 groups: 8-11 years, 12-17 years, and 18-36 years. Pearson Chi square test was done to test the association between age group and distribution of skeletal jaw base relationship. All data were recorded and analyzed with SPSS software. Result: The distribution of skeletal malocclusion according to ANB angle classification revealed that the most prevalent skeletal malocclusion was Class II skeletal jaw base relationship accounting up to 97(48.5%), followed by Class I 87(43.5%) and Class III 16(8%). The study showed statistically significant difference between gender and distribution of skeletal jaw base relationship (p<0.05). However, there was no significant difference between the age groups and distribution of skeletal jaw base relationship (p<0.05). Conclusion: Most common skeletal jaw base relationship in patients seeking orthodontic patients was Class II followed by Class I and Class III in a tertiary center of mid-western Nepal.